Estudo dos mecanismos envolvidos na reabsorção óssea alveolar induzida pela deficiência de estrógeno - Soraia Macari (2015)
INTRODUCTION: Throughout the immediate postmenopausal first years, decreased estrogen levels lead to rapid bone loss that may lead to an osteoporosis process. Estradiol (E2) mechanism of action remains unclear, despite of it well-established effect of on bone cells. Bone remodeling/resorption also depends on cytokines and chemokines, thus it is clear the necessity to better understand the relationship between E2 and chemokines in pathologic condition as osteoporosis. PURPOSE: 1. To evaluate the effect of estrogen-deficiency and E2 replacement in the mice alveolar bone microarchitecture; 2. To evaluate the effect of estrogen receptor ER in alveolar bone and mechanical loading-induced bone remodeling; 3. To determine the effect of ST2/IL-33 in alveolar bone loss by ovariectomy (OVX) and mechanical loading-induced bone remodeling. METHODOS: Purpose 1. C57BL6/J and Balb/c mice were OVX and implanted with oil- (OVX) or 17-estradiol (E2)-containing (OVX+E2) capsules. Ovary-intact mice were used as controls. Euthanasia was achieved 15 and 30 days after OVX and maxillary bone were collected for micro computed tomography (microCT) analysis and ELISA and femur for histomorphometric analysis; Purpose 2. The alveolar bone and mechanical loading induced bone of females and males homozygote ER+/+ (wild type - WT) and ER-/- (ERKO - estrogen receptor knockout) mice were submitted to microCT, RT-PCR and energy dispersive spectroscopy (EDS). WT and ERKO mice bone marrow cells (BMC) were differentiated into osteoblasts and osteoclasts cell culture; Purpose 3. Balb/c (Wilde-type-WT) and ST2-/- mice were ovariectomized and implanted with oil- (OVX) or E2-containing capsules (OVX+E2). Maxillary bones submitted or not to mechanical loading were analyzed by histology and histomorphometric analysis, RT-PCR and bone marrow cells (BMC) were isolated to osteoclasts differentiation. RESULTS: Purpose 1. As determined by maxillary alveolar bone microCT analysis, OVX mice displayed decreased trabecular thickness, bone density and bone volume, and increased trabecular separation. A significant loss of alveolar bone crest was also associated with ovariectomy. These effects were associated with a reduction of trabecular bone percentage and cortical thickness in the femur. The E2 replacement fully prevented ovariectomy-induced alterations in the alveolar and femoral bones. Moreover, TNF- levels and RANKL/OPG ratio were increased in the maxilla after OVX, and these responses were also reversed by E2. Purpose 2. Maxillay alveolar bone loss and orthodontic tooth movement (OTM) were augmented in female and male ERKO mice and associated with decreased calcium percentage levels and increased expression IL-33 in periodontium. Both genders ERKO demonstrated an osteoporotic phenotype in the femur and vertebrae. In vitro results showed increased osteoclasts and osteoblasts differentiation from BMC in ERKO mice compared to WT mice; Purpose 3. IL-33 receptor deficiency, ST2, caused bone loss in femur and maxillary bone. Similar effects of OVX (loss of bone mass) were observed in long bones of WT and ST2 deficient mice. However, the ovariectomized ST2-/- mice maxillary bone did not exhibit bone loss. Moreover, under mechanical loading-induced bone remodeling, E2 and ST2 individually yielded bone protection, but the phenotype was reversed by their complete absence (ST2-/- OVX mice). In vitro results confirmed that E2 and IL-33 were able to suppress osteoclasts formation. Nevertheless, when BMC were taken from OVX mice, IL-33 treatment did not affect osteoclasts differentiation. CONCLUSION: Estrogen lack will lead to alveolar bone loss in maxillary bone with TNF- and RANKL/OPG ratio increase. Our results suggest that E2 acts through ER in the alveolar bone and that maxillary alveolar bone loss, caused by estrogen lack, might be associated with increased IL-33 levels. However, the "osteoprotective" effect of IL-33/ST2 in alveolar bone is not observed under the condition of estrogen deficiency